Tantangan Guru Dalam Pembelajaran Daring Pada Masa Pendemi Di SD Negeri 01 Kebandungan Kecamatan Bantarkawung - Haryati, Juju Ariah Tati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This paper examines the implementation of education policies during the Covid-19 pandemic related to distance learning policies. The distance learning process is a solution that is not yet optimal in its implementation. The purpose of writing this article is to display and desciprtion challenges faced by teachers in the learning process during the pandemic in the SD Negeri 01 Kebandungan, Kecamatan Bantarkawung. This study used a descriptife qualitative. The results of this study prove that, (1) the family economy burdens the problems of the primary needs of parents lives, (2) parental education can affect how parents guide and care for their children while are learning at home, and (3) limited learning resourc as having to have an andorid based phone, data, and signal become obstacles in the learning process.